Development of FBG Sensing System for Outdoor Temperature Environment - S. Daud; M.A. Jalil; S. Najmee; Saktioto Saktioto; J. Ali; P.P. Yupapin (My University, 2011)
We have experimentally designed a practical pass-through type FBG temperature sensor. The objective of this study is to design and built a prototype outdoor fibre Bragg grating (FBG) temperature sensor system. Its performance is evaluated at different times of the day. In order to reduce the optical losses of the FBG system, the shortest optical fiber path used to connect the FBG system is 55.5m. It has a total connector loss 4.0 dB and fibre loss of 0.3 dB thus giving a total loss of the system as 4.3 dB. The FBG sensor system is connected to the tunable laser source (TLS) and optical spectrum analyzer (OSA). The TLS is used to provide a broadband light source via a fibre optic cable of wavelength 1550 nm. The OSA is used to display the transmission and reflection spectrum to give the Bragg wavelength _B, bandwidth and power dip. The output spectrum can be obtained through direct connection to the FBG. Result of transmission and reflection spectrum show the sensitivity which is calculated from the slope of the graph. The FBG temperature sensor system has an average sensitivity of 9.1 pm (°C)-1 based on the transmission spectrum. It has an average sensitivity of 10.6 pm (°C)-1 based on the reflection spectrum.
Keywords: Advanced Fiber Optic Sensors